Tepung Tawar: Keanekaragaman Hayati dan Jejak Budaya di Pegunungan Meratus - Royyani, Mohammad Fathi (JURNAL BIOLOGI INDONESIA, 2014)
The biodiversity used by people as a form of interaction between humans and the environment. The biodiversity isa footstep of the interaction among humans. Tepung Tawar is the concept of biodiversity utilization by localcommunality. It is only the interaction between biodiversity and user but beyond biodiversity utilization namelythe interaction among the local. Through ethnographic studies, it is known that the use of plants by Meratuspeople have long history. In this case, tepung tawar is the field in which humans perform another interpretation ofreality. Tepung tawar also is agreement between the two traditions together to save the practices commonlyperformed by the public, religiously and traditionality.Keywords: biodiversity, custom, meratus, mutual interaction, religion